2021
DOI: 10.1108/ijhrh-11-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Failing the rights: sexual vulnerability, access to services and barriers to contraceptives among adolescents in Narok County, Kenya

Abstract: Purpose Around one in five girls in Kenya, aged 15 to 19 years old are either pregnant or have given birth. Of 47 counties, adolescent pregnancy is highest in Narok, where about 40% of girls aged 15 to 19 years old have begun childbearing. This study aims to explore drivers to sexual activity, access to sexual and reproductive health (SRH) services and barriers to contraceptive use among adolescents in Narok County, Kenya to inform the design of SRH interventions and safeguard young people’s rights to sexual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Secondly, it could be due to limited quality health services, myths and misconceptions as factors that affected FP use at the time of relocation to another country before being settled in a host community. This concurs with several studies [ 39 41 ] which revealed that weak health system and poor health services affect the use of FP.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, it could be due to limited quality health services, myths and misconceptions as factors that affected FP use at the time of relocation to another country before being settled in a host community. This concurs with several studies [ 39 41 ] which revealed that weak health system and poor health services affect the use of FP.…”
Section: Discussionsupporting
confidence: 93%
“…From focused group discussions with the adolescents and key informant interviews with their caregivers, health workers, and community leaders, open discussions on sex and sexuality among girls and their parents or caregivers were less frequent because this was considered against community norms. 7 This mirrors what has been reported in other studies in Africa where boys are stereotyped as sexually active, girls as sexually restrained, and societies believe that the sexual agency of girls should be restricted as a way of protecting the girls. 8 Such gender norms are established early in life and have a substantial impact on adolescent girls' agency.…”
Section: Gender Social and Economic Inequality Among Adolescents In K...supporting
confidence: 81%
“…6 In 2019, we did a mixed methods study on adolescent pregnancy and SRH rights among Kenyan boys and girls aged 15 to 19 years old. 7 From this study, adolescent boys reported greater access to SRH information and services, were more knowledgeable about SRH topics, including contraceptive methods, and were more likely than girls to have dialogues about sex and ll Med 3, 361-368, June 10, 2022 365 Commentary sexuality with their parents and caregivers. From focused group discussions with the adolescents and key informant interviews with their caregivers, health workers, and community leaders, open discussions on sex and sexuality among girls and their parents or caregivers were less frequent because this was considered against community norms.…”
Section: Gender Social and Economic Inequality Among Adolescents In K...mentioning
confidence: 83%
See 1 more Smart Citation
“…However, teens (10 to 19 years) are the most susceptible to the negative effects of unprotected sex because, according to UNICEF, these behaviours are linked to two-thirds of adult premature deaths and one-third of the entire burden of diseases [ 8 ]. Drug use, poor parenting, peer pressure, sociocultural standards, mass media, and individual sexual attitudes are all occasionally associated with the behaviours [ 9 , 10 ]. Unsafe sexual behaviours are a health determinant that is frequently connected to unintended pregnancies and the obstetric outcomes they are associated with, such as anemia, puerperal psychosis, eclampsia, fistula, abortion, and hemorrhage, to name a few, as well as new STIs/HIV infections [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%